Characterisation of PRT1, an E3 Ligase of the N-end Rule Pathway in Arabidopsis thaliana - Till, Christopher John (2019)
The N-end rule pathway of targeted protein degradation links the half-life of a protein to the identity of its amino (N-) terminal residue. Proteins become substrates for the pathway following proteolytic cleavage which may be followed by enzymatic modification to produce novel N-termini. In Arabidopsis thaliana, proteins with aromatic N-termini are targeted for degradation by the PROTEOLYSIS1 (PRT1) E3 ligase (Potuschak et al., 1998). This component of the plant N-end rule pathway has received little attention by the scientific community with no definitive physiological role or substrate profile established to date.